Pengaruh Gross Domestic Product (GDP) terhadap Tingkat Kemiskinan di Indonesia dengan Zakat Distribution sebagai Variabel Moderasi pada Tahun 2011-2020 - Abdullah Yuqdha Ada'uddin; Indah Yuliana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to examine effect of the Gross Domestic Product variable on the poverty level in Indonesia with the distribution of zakat as a moderating variable. The research method that we use is descriptive quantitative research with secondary data types that can be accessed through the website of the Indonesian Central Statistics Agency (BPS) and the PPID Baznas RI Information Management and Documentation Officer website. Data analysis was carried out using the eview 12 application to determine the effect of Gross Domestic Product on poverty levels in Indonesia. Then, the Moderated Regression Analysis (MRA) test was conducted to find the moderating effect of zakat distribution on the relationship between gross domestic product and poverty level in Indonesia. The results showed that the Gross Domestic Product had no significant effect on the poverty level in Indonesia. Meanwhile, the moderation test conducted shows that the distribution of zakat does not directly moderate the relationship between gross domestic product and the poverty level in Indonesia.